Antinociceptive local effect of the combination of dexketoprofen trometamol and chlorhexidine gluconate in a formalin test: an additive effect (Brazilian Journal of Pharmaceutical Sciences, 2018)
A drug delivery system (DDS) with analgesic and antibacterial properties would be desirable for the local control of post-operatory pain and the prevention for surgical site infection (SSI). The objective of the present study was to evaluate the antinociceptive effect of the combination between dexketoprofen trometamol (DXT) and chlorhexidine gluconate (CHX) in the formalin pain model. Different doses of CHX were combined with DXT and were locally administered in rats paw simultaneously with 5% formalin dilution. Flinches were documented and the antinociceptive effect was calculated. The area under the curve of each experimental group were calculated and the % of antinociception were compared. The groups of CHX and DXT showed similar antinociceptive effect. The combination groups (DXTCHX) showed higher antinociceptive effect that the one obtained with individual molecules. Besides the confirmation of DXT local antinociceptive properties, CHX also showed a positive effect; and an additive effect when combined with DXT.